Pengaruh Pelatihan Kerja dan Beban Kerja terhadap Produktivitas Kerja Pegawai Pada Rumah Sakit Ibu dan Anak XYZ Jombang - Nilna Muna Putri; Agus Frianto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
This research aims to determine: The influence work training and work overload on work productivity employees medic at hospital mother and child xyz Jombang. This resarch is a aprroach asosiatif resarch with quantitative research. The population in this study were whole permanent medic employees hospital mother and child xyz jombang. The sampling technique uses saturated sampling with a total sample of 76 employees. Data collection techniques using a quesstionnaire tha has been tested for validity and reliability. The classic assumption test includes the normality test, the multicollinearity test, the heteroscedasticity test, the autocorrelation test and the collinearity test. Multiple linear regression analysis to test and prove the research hypothesis. The result of the t-test (partial)showed that the work training (X1) had a positive and significant effect on work productivity employees (Y) and the work overload (X2) had a positive significant effect on work productivity employees (Y). The result of the F test (simultaneous) showed that the work productivity (X1) and work overload (X2) as a whole had simultaneous and significant effect on work productivity (Y).Keywords: Work Training; Work Overload; Work Productivity